An evaluation of factors associated with safe infant sleep practices among perinatal home visiting participants in Florida, United States. (March 2023) - Dorjulus, Barbara; Prieto, Concha; Elger, Rafaella S; Oredein, Igbagbosanmi; Chandran, Vidya; Yusuf, Bola; Wilson, Roneé; Thomas, Nicholas; Marshall, Jennifer
Sleep-related deaths are a leading cause of infant mortality in Florida. The American Academy of Pediatrics recommends placing infants to sleep on their back, alone, and without soft bedding. Compliance with these guidelines varies among parents. This evaluation examined the rates of safe infant sleep practices and associated factors among 1985 participants enrolled in Florida Maternal, Infant, and Early Childhood Home Visiting (FL MIECHV) programs during 2017–2019. Participant- and program-level variables were examined in relation to three sleep practices: infant position, bedding, and bed-sharing at 2–3 months to determine which factors were associated with high rates of safe sleep outcomes. Analyses included univariate descriptive statistics, bivariate statistics, and multivariable logistic regression. Most caregivers (70%) reported always placing their babies to sleep on their back, alone, and without soft bedding. Factors such as primary language, race, education, housing situation, and year the Safe Baby™ curriculum implemented were significantly associated with safe infant sleep practices. Bearing this in mind, FL MIECHV can tailor safe sleep education, messaging, and strategies to support participants at highest risk. Recent adoption of the Safe Baby™ curriculum, and associated staff training, was an important factor influencing parents' infant sleep practices.